[73] Outcomes of patients with advanced clear-cell renal cell carcinoma treated by sunitinib as first-line therapy: A prospective observational study in real-world practice of the Academic Hospital of Oran, Algeria - Nadia Ameziane (Taylor & Francis Group, 2018)
Objective: To investigate the effectiveness of sunitinib as first-line therapy in real-world practice in terms of progression-free survival (PFS), objective response rate (ORR), and overall survival (OS), and to evaluate the safety profile for advanced or metastatic clear-cell renal cell carcinoma (ccRCC).There is lack of published Algerian prospective data in advanced RCC. Methods: An observational prospective study was conducted at the Medical Oncology Department of the Academic Hospital of Oran between January 2012 and May 2015. Patients enrolled were aged >18 years, with untreated ccRCC with a Karnofsky performance status (KPS) >70%. Sunitinib was administered with schedule of 50 mg/day, 4-weeks on/2-weeks off. Dose adjustment and changing schedule to 2-weeks on/1-week off, were possible in cases of persistent severe toxicity. Results: In all, 43 patients with advanced or metastatic ccRCC were enrolled in the study. The sex ratio was 1.8, with a mean (SD) age of 58.4 (3.5) years. The KPS was 100%, 80–90% and 60–70% in 11%, 77% and 12% of the patients, respectively. In all, 339 cycles were administered, with a mean (SD; range) of 11.6 (2.8; 1–42) cycles. The median PFS by intention-to-treat (ITT) was 10.5 months (95% confidence interval [CI] 6.1–14.9) with a PFS rate at 12 months of 34.8%. The ORR in ITT was 45% (95% CI 30–60). The median OS was 21.3 months (95% CI 11.5–31.07) with an OS rate at 2-years of 30.2%. The main grade 3–4 toxicities were represented by asthenia (56%), anorexia (32%), hand-foot syndrome (33%), stomatitis (28%), diarrhoea (23%), hypertension (21%), and thrombocytopaenia (14%). Conclusions: The effectiveness results of sunitinib in our present study are similar to those in the literature, with a manageable and acceptable toxicity profile.